KONSTRUKSI MAKNA KENCAN DI SITUS PENCARIAN JODOH TINDER (Studi Fenomenologi Pada Pria Pengguna Tinder Di Jakarta) - Fridha, Merry; Octavianti, Meria (Universitas Merdeka Malang, 2016)
Abstract The use of a mate search application is currently being used by the people of Indonesia crowded. This is evidenced by the number of applications such as beetalk mate search, meowchat, OkCupid, tinder and much more. Mate search site can be trusted to provide solutions for speed and accuracy of the arrival of a mate for its users. This phenomenon will create a shift in meaning where in the past dating dating will be conducted by a couple who have gone through the introductory stage, approach, new assessment followed by a date. But today the stage is shortened to introduction through tinder mate search application, and then meet for a date. So dating conducted a blind date (blind date) because the two people familiar with the dating without opponents date. This attracted the attention of researchers so that researchers intrigued to know how meaning construction dating site matchmaking search Tinder (Phenomenology Study on Men Tinder Users in Jakarta). The theory used in this research is the theory of Computer Mediated Communication (CMC) and the Social Penetration Theory. With Qualitative research methodologies and approaches phenomenology, the study provides an overview of Constructivist paradigm will shift the meaning of dating for men dating search app users in the application tinder. The results showed that male informants in Jakarta tinder users will choose a date, like selecting items preferably in the online shop. If they like the woman then they will be invited to meet and relationships can be moved quickly towards the dating stage. Meaning of dating that is identified with the stages of relationship